ANALISIS PENYIMPANAN BERAS MELALUI PERUM BULOG SUB DIVRE PEKALONGAN TERHADAP KESTABILAN HARGA - Yusuf Enril Fathurrohman; Restu Pambudi (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2020)
Perum BULOG Pekalongan Sub-Divre is responsible not only for storing rice but also having responsibility for price stability. This study aims to determine the flow distribution of Bulog rice, rice criteria and the role of Perum BULOG Pekalongan Sub-Divre on price stability. The analytical method used is descriptive analysis and using primary and secondary data.The results showed that the Plot of Perum BULOG Pekalongan Sub-Divre did not differ from the central regulation, which used 3 channels (SATGAS AD DN, UPGB and Partners). The types of rice managed by Bulog are Raskin (medium) and commercial (premium) rice with applicable criteria. Meanwhile, to maintain the stability of rice prices, the Pekalongan Public Logistics Agency (Perum Bulog) conducts market operations at 10 distribution points and provides Raskin to Poor Households (RTM).